Knowledge and Application of Pharmacist Ethical Practices in Surakarta City - Denise Pasesa, Rara; Da'i , Muhammad (Journal La Medihealtico, 2024)
This study aims to determine the knowledge and application of pharmacist ethical practices in the city of Surakarta. This research is a type of descriptive research. This research was conducted in all pharmacies and hospitals in the Surakarta City area. Data collection will take place in November 2023-January 2024. The population in this study was 489 and the error rate was 5%, so the sample taken was 205 people. The selection of respondents in this study was carried out by non-probability sampling techniques with a sampling technique, namely purposive sampling. The instrument used in this study was a questionnaire. Data analysis of this study was carried out by descriptive analysis on SPSS software. Based on the results of the study, pharmacists were dominated by good knowledge as many as 132 respondents (64%) while for the application of pharmacist ethical practices in Surakarta City was dominated by the application of ethics as many as 122 respondents (60%). This study concludes that pharmacists in Surakarta City have good knowledge of ethical practices and sufficient application of ethical practices.